Evaluation of the Contribution of Deposited Precipitation - Jaroslav Fišák; Miroslav Tesař (Advances in Meteorology)
Main topic of this study is evaluation of the contribution of deposited precipitation (DP) to the falling precipitation (FP) amount. An automatic device for DP weight measurement developed and produced at the Institute of Atmospheric Physics was used. The tipping bucket rain gauges were used for the FP measurement. Present paper summarizes the results of measurements of deposited and falling precipitation in three localities: Suchdol, Prague (capital of the Czech Republic), Poledník (Bohemian Forest), and Smĕdava (the Jizerské hory Mts.). Two later introduced stations are situated in the mountainous part of the Czech Republic. For each of mentioned stations the daily averages of the DP totals were determined by the values 0.074 mm for Suchdol, 0.112 mm for Poledník, and 0.103 mm for Smĕdava. Further the mean daily DP sums were evaluated for the days with the occurrence of this precipitation only by the values 0.136 mm, 0.276 mm, and 0.289 mm for the stations Suchdol, Poledník, and Smĕdava, respectively. Obtained results were compared with the findings published in the literature. In each of the stations the ratio between the deposited and falling precipitation was determined as well. For the Suchdol this ratio reached 95.2% in December 2013.